Fatores que determinam o desenvolvimento rural nas microrregiões do Brasil - Alysson Luiz Stege; José Luiz Parré (Confins)
Rural development in Brazil’s microregions: a multidimensional study. Because the rural Brazilian population has heterogeneous characteristics of social, technical and regional aspects, we studied how the rural development is distributed all over Brazil. The objective of this paper is to analyze the rural development in the Brazilian microregions, inserted in the multidimensional context of the rural development. By using the technique of multivaried statistics, more specifically the factorial analysis, a synthetic index is produced, the rural development index, which will be used for the 558 Brazilian microregions. The results indicate a very heterogeneous rural development in the microregions, and that the rural development process is more than the analysis of the economic growth calculated by the product and income per capita, because factors were found in relation to the well-being of rural domiciles, environment, educational system and others.